A Case Report on Maxillary Ameloblastic Fibroma in a 55-Year-Old Man - Ma. Elline Faye Mendoza; Irlan Altura (Philippine Journal of Otolaryngology Head and Neck Surgery)
Ameloblastic Fibroma (AF) accounts for only 2% of all odontogenic tumors.1 It has been shown to be more common in males than females.2 A malignant transformation of this tumor is known as ameloblastic fibrosarcoma. To the best of our knowledge, there are no published reports on AF in the Philippines, with only one report of its malignant counterpart, ameloblastic fibrosarcoma.3 We present a rare case of AF with an unusual presentation and discuss its rarity, pathogenesis, histologic features and management.